The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2005
DOI: 10.1590/s0100-204x2005000900011
|View full text |Cite
|
Sign up to set email alerts
|

Soluções nutritivas para cultivo e produção de frutanos em plantas de Vernonia herbacea

Abstract: Pesq. agropec. bras., Brasília, v.40, n.9, p.911-917, set. 2005 Soluções nutritivas para o cultivo de Vernonia herbacea 911 Soluções nutritivas para cultivo e produção de frutanos em plantas de Vernonia herbaceaGeraldo Rogério Faustini Cuzzuol (1) , Maria Angela Machado Carvalho (2) , Lilian Beatriz Penteado Zaidan (2) e Pedro Roberto Furlani , foi comparada com a de Hoagland nas forças iônicas de 50%, 100% e 200%. Foram realizadas duas avaliações para análise de crescimento e conteúdo de frutanos. As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Half of the plants received ambient CO 2 (380 ± 20 ppm) and half received elevated CO 2 (760 ± 50 ppm) provided from a cylinder containing 99.8% CO 2 . During 21 days of acclimation, plants received 100 ml Vernonia nutrient solution per week (Cuzzuol et al. 2005) and were further irrigated with water to keep soil moist.…”
Section: Methodsmentioning
confidence: 99%
“…Half of the plants received ambient CO 2 (380 ± 20 ppm) and half received elevated CO 2 (760 ± 50 ppm) provided from a cylinder containing 99.8% CO 2 . During 21 days of acclimation, plants received 100 ml Vernonia nutrient solution per week (Cuzzuol et al. 2005) and were further irrigated with water to keep soil moist.…”
Section: Methodsmentioning
confidence: 99%
“…The chemical composition of leaves of V. herbacea was determined in the Laboratório do Centro de Solos e Recursos Agroambientais do Instituto Agronômico de Campinas (IAC) and a specific nutrient solution was elaborated to supply adequate nitrogen requirement as previously determined by Cuzzuol et al (2005) (Hoagland and Arnon, 1938) and the pH was adjusted to 5.5-6.0 with 1N KOH. Plants were separated in two groups that received 100 mL of one of the above solutions each week.…”
Section: Methodsmentioning
confidence: 99%
“…However, more recently Cuzzuol et al (2003) showed that in a narrow range of low concentrations, nitrogen promoted growth and inhibited fructan accumulation and plant productivity in field grown plants, whereas the opposite was found when higher nitrogen concentration was supplied. The chemical composition of leaves of V. herbacea allowed us to define nitrogen requirement of these plants (Cuzzuol et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Previous results with V. herbacea showed that the ideal nitrogen concentration for plant growth is 10.7 mmol L -1 N-NO 3 -and that 1.3 mmol L -1 N-NO 3 -provides a limiting growth condition (Cuzzuol et al 2005a). Therefore, the use of this N-limited concentration satisfies the criteria established for the study of a specific stress factor.…”
Section: Introductionmentioning
confidence: 85%
“…Rusby (Herbarium number: SP169567) were obtained and cultivated as described by Cuzzuol et al (2005b). Plants received, weekly, 100 mL of a specific nutrient solution containing 10.7 mmol L -1 N-NO 3 -, elaborated to supply adequate nitrogen required by V. herbacea as previously determined by Cuzzuol et al (2005a). After twelve months of growth, half of the plants continued to receive the same solution (control plants) while the other half received an N-limited nutrient solution (1.3 mmol L -1 N-NO 3 -), according to Cuzzuol et al (2005a).…”
Section: Methodsmentioning
confidence: 99%